OS SHAKEMAPS DO SISMO DE ARRAIOLOS DE 15 DE JANEIRO DE 2018 (ML 4.9) - Marreiros, Célia (2019)
On the 15-01-2018, after the occurrence of the earthquake of magnitude 4.9 ML at the region of Arraiolos, maps were produced automatically to characterize the impact of the earthquake [seismic intensity (Mercalli Modified scale, 1956), peak acceleration (PGA) and peak velocity (PGV)], using a modified version of the software ShakeMap made available by the U.S. Geological Survey (USGS). The maps produced (shakemaps) are based on regional constraints of data observed and local amplifications. The addition of 1 observed data, as they are available, introduce improvements at the quality of the maps. In particular, the maps produced with the integration of macrosseismic observations are more consistent with these observations. In this work we will present the effect of the constraints made by the macrosseismic results of the earthquake of Arraiolos, at the automatic process of characterization of the impact of the earthquakes at Portugal mainland